Association of Bleeding Disorders and Risk of Complications Following Open Reduction and Internal Fixation of the Ankle. Issue 4 (November 2022) - Malyavko, Alisa; Quan, Theodore; Stoll, William T.; Manzi, Joseph E.; Gu, Alex; Tabaie, Sean; Stein, Benjamin E.
Category: Ankle; Other Introduction/Purpose: Open reduction and internal fixation (ORIF) of the ankle is a common procedure performed to correct ankle fractures in many different patient populations. Diabetes, peripheral vascular disease, and osteoporosis have been identified as risk factors for postoperative complications following surgery for ankle fractures. To date, there have not been any studies evaluating postoperative outcomes in patients with bleeding disorders undergoing operative treatment for ankle fractures. The aim of this study was to determine the postoperative complication rate following ORIF of the ankle in patients with a bleeding disorder versus those without a bleeding disorder. Methods: From 2006 to 2018, patients undergoing operative treatment for ankle fracture were identified in the National Surgical Quality Improvement Program database. Two patient cohorts were defined: patients with a bleeding disorder and patients without a bleeding disorder. Patients who underwent either inpatient or outpatient ORIF of the ankle were included in this study. In this analysis, demographics, medical comorbidities, and postoperative complications variables were assessed between the two cohorts. Bivariate and multivariate analyses were performed. Results: Of 10, 306 patients undergoing operative treatment for ankle fracture, 9, 909 patients (96.1%) had no bleeding disorder whereas 397 patients (3.9%) had a bleeding disorder. Following adjustment on multivariate analysis, compared to patients who did not have a bleeding disorder, those with a bleeding disorder had an increased risk of any postoperative complications (OR 1.479; p=0.024), requirement for postoperative blood transfusion (OR 2.863; p=0.001), and extended length of hospital stay greater than 5 days (OR 1.455; p=0.010) (Table 1). Conclusion: Patients with bleeding disorders are at an increased risk of postoperative complications following ORIF for ankle fractures. Our study found that patients with bleeding disorders had greater odds of postoperative complications following ORIF of the ankle. Determining patient risk factors and creating optimal preoperative and perioperative management plans in patients with bleeding disorders undergoing ORIF can be beneficial in reducing postoperative complications, improving patient outcomes, and reducing overall cost.